Tính nguyên hàm `∫1/(sqrt(x+1)+sqrtx+1)dx`

Tính nguyên hàm `∫1/(sqrt(x+1)+sqrtx+1)dx`

0 bình luận về “Tính nguyên hàm `∫1/(sqrt(x+1)+sqrtx+1)dx`”

  1. Đáp án:

     

    Giải thích các bước giải: Một cách để tham khảo

    $\dfrac{1}{\sqrt{x + 1} + \sqrt{x} + 1} = \dfrac{(\sqrt{x} + 1) – \sqrt{x + 1}}{(\sqrt{x} + 1)² – (\sqrt{x + 1})²}$

    $ = \dfrac{\sqrt{x} + 1 – \sqrt{x + 1}}{2\sqrt{x}} = \dfrac{1}{2} + \dfrac{1}{2\sqrt{x}} – \dfrac{\sqrt{x + 1}}{2\sqrt{x}}$

    Đặt $: t = \sqrt{x} ⇒ t² = x; dt = \dfrac{dx}{2\sqrt{x}}$

    Tính $:∫\dfrac{\sqrt{x + 1}}{2\sqrt{x}}dx = ∫\sqrt{t² + 1}dt$

    $ = \dfrac{1}{2}t\sqrt{t² + 1} + \dfrac{1}{2}ln(t + \sqrt{t² + 1}) + C_{1}$

    $ = \dfrac{1}{2}\sqrt{x(x + 1)} + \dfrac{1}{2}ln(\sqrt{x} + \sqrt{x + 1}) + C_{1} $

    $ ⇒ ∫\dfrac{1}{\sqrt{x + 1} + \sqrt{x} + 1}dx = ∫\dfrac{1}{2}dx + ∫\dfrac{1}{2\sqrt{x}}dx – ∫\dfrac{\sqrt{x + 1}}{2\sqrt{x}}dx$

    $ = \dfrac{x}{2} + \sqrt{x} – \dfrac{1}{2}\sqrt{x(x + 1)} – \dfrac{1}{2}ln( \sqrt{x} + \sqrt{x + 1}) + C$

     

    Bình luận
  2. Đáp án:

    $\dfrac12\left(\sqrt x +\sqrt{x+1}\right) – \dfrac12\ln\left(\sqrt x +\sqrt{x+1}\right)- \dfrac{1}{2\left(\sqrt x +\sqrt{x+1}\right)} + \dfrac{1}{4\left(\sqrt x +\sqrt{x+1}\right)^2}+ C$

    Giải thích các bước giải:

    $\quad I =\displaystyle\int\dfrac{1}{\sqrt{x+1} +\sqrt x +1}dx$

    Đặt $t = \sqrt x + \sqrt{x+1}$

    $\to \dfrac{1}{t}= \sqrt{x+1} -\sqrt x$

    $\to t -\dfrac1t = 2\sqrt x$

    $\to \dfrac14\left(t-\dfrac{1}{t}\right)^2 = x$

    $\to \dfrac12\left(1 +\dfrac{1}{t^2}\right)\left(t -\dfrac1t\right)dt = dx$

    $\to \dfrac{t^4 -1}{2t^3}dt = dx$

    Ta được:

    $\quad I =\displaystyle\int\dfrac{1}{1+t}\cdot \dfrac{t^4 -1}{2t^3}dt$

    $\to I = \dfrac12\displaystyle\int\left(1 -\dfrac1t +\dfrac{1}{t^2} -\dfrac{1}{t^3}\right)dt$

    $\to I = \dfrac12t-\dfrac{1}{2}\ln|t|  – \dfrac{1}{2t} +\dfrac{1}{4t^2} + C$

    $\to I = \dfrac12\left(\sqrt x +\sqrt{x+1}\right) – \dfrac12\ln\left(\sqrt x +\sqrt{x+1}\right)- \dfrac{1}{2\left(\sqrt x +\sqrt{x+1}\right)} +\dfrac{1}{4\left(\sqrt x +\sqrt{x+1}\right)^2}+ C$

    Bình luận

Viết một bình luận